Rent filmed live on Broadway. The final performance - Larson, Jonathan 1960-1996 (Sony Pictures Home Entertainment, 2009)
An intimate journey through a single year in the lives of a small circle of friends and artists living their dreams, battling their demons and celebrating life on the streets of New York City's East Village. Mark is a would-be filmmaker, Angel is a sweet transvestite, Mimi is an exotic dancer who confront the challenges of poverty, mortality and paying the Rent
Title from container
Originally directed for the stage by Michael Greif ; originally produced for the stage by Jeffrey Seller, Kevin McCollum, Allan S. Gordon and New York Theatre Workshop
Special features: "Rent, the final days on Broadway:" a retrospective documentary; "The final curtain call:" past & present cast members sing "Seasons of Love" on stage one last time; "Home:" one last look at the theater that became the home for Rent; "The wall:" a rare look at the famous backstage wall; "The final lottery:" hundreds of fans hope to be chosen to sit in the front 2 rows
Keywords: AIDS (Disease) / Drama; Man-woman relationships / Drama; Interpersonal relations / Drama; Apartment dwellers / Drama; Youth / New York (State) / New York / Drama; Youth / Psychology / Drama; AIDS (Disease); Apartment dwellers; Bohemianism; Drug addicts; Gay men; Homeless persons; Interpersonal relations; Man-woman relationships; Youth; Youth / Psychology; New York (State) / New York; Feature films; Fiction films; Musical films; Video recordings for the hearing impaired; Film; DVD-Video